Contribution to the knowledge of Lepidoptera Noctuidae of Po Valley (Northern Italy) (Bollettino di zoologia agraria e bachicoltura, 2024)
Lepidoptera Noctuidae has been monitored in the Po Valley (Northem Italy) during an eight year period (1989-1996).Pheromone traps of different shapes and light traps have been used. Pheromone traps have been checked 12 months every year. The list of the caught species is given.A comparison between the data collected in the area under investigation and the surrounding ones has been performed.Among the species found, some have never been reported in the area: Aletia impura (Hiibner), Ctenoplusia accentifera (Lefebvre), Spaelotis ravida (Denis & Schiffermiiller), Xestia sexstrigata (Haworth) and Meganephria bimaculosa (Linné).
Keywords: Lepidoptera Noctuidae; light trap; pheromone trap; Northern Italy